Anxiety, Loneliness, Drug Craving, and Depression Among Substance Abusers in Sichuan Province, China - Chen, Xin; Qiu, Nan; Zhai, Liang; Ren, Gui (Frontiers in Pharmacology, 2021)
Studies have reported that anxiety had a positive effect on depression among substance abusers in males. However, little is known about the mechanism underlying this relationship in substance abusers in males. The purpose of this study was to investigate the mediating effect of loneliness and drug craving between anxiety and depression in substance abusers in males. State-Trait Anxiety Inventory, The UCLA Loneliness Scale, Drug Craving Scale, and The Center for Epidemiologic Studies Depression Scale were employed into this study to investigate 585 substance abusers in males (age range of 20–58 years: M = 33.21, SD = 6.97). Structural equation modeling and the bootstrap approach were used to analyze the mediating effect of loneliness and drug craving on the relationship between anxiety and depression. The results indicated that: Loneliness had a significant positive correlation with anxiety (r = 0.37, p < 0.001) and depression (r = 0.49, p < 0.001); Drug craving had a significant positive correlation with anxiety (r = 0.28, p < 0.001) and depression (r = 0.39, p < 0.001). Loneliness and drug craving mediated the link between anxiety and depression. There was a significant positive correlation between substance abusers in male’s anxiety, loneliness, drug craving, and depression. Loneliness and drug craving had a significant mediating effect on the relationship between anxiety and depression. Therefore, it was suggested that substance abusers in male’s anxiety and depression might be improved and driven by decreasing loneliness and drug craving. Targeted interventions to decrease substance abusers in male’s loneliness and drug craving should be developed, implemented, and help them to recover.